ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE OF SME EXPORTS IN CENTRAL JAVA THROUGH EXPORT MARKETING STRATEGIES - Handayani, Emilda; Ferdinand, Augusty Tae; Sugiono, Sugiono (Master of Management Diponegoro University, 2017)
The Era of the ASEAN Economic Community (MEA) should be a boost for small and medium entrepreneurs (SMEs) to be more proactive in maintaining the existence of their business. SMEs as one of the important links in Indonesia's economic growth, need to get special attention to develop it. The research problem is how to improve export performance of SMEs in Central Java through the adoption of e-commerce, 3PL (third party logistics support), export market orientation and export marketing strategy. In answer to the problem developed a modeling and four hypotheses have been formulated in this study. This study used sampling purposive sampling method in which the respondent is the owner or manager of SMEs in Central Java that meets the criteria. The number of samples in this study was 134 respondents. The analysis tool used is SEM (structural equation modeling) in the AMOS program. The result of SEM analysis meets the criteria of Goodness of Fit that is Chi-square equal to 193,647; probability 0.051; TLI 0.981; CFI 0.984; CMIN / DF 1,188; RMSEA 0,039; GFI 0.879 and AGFI 0.844. The results of the data analysis showed that all hypotheses are accepted and produced three strategies in order to improve export performance through export marketing strategies that are influenced by export marketing orientation, support from logistic companies, and e-commerce adoption. Keywords: Small and Medium Enterprises, Export Performance, Export Marketing Strategy, Export Marketing Orientation, Logistic Support Company, and E-Commerce Adoption